2011
DOI: 10.1186/1471-230x-11-135
|View full text |Cite
|
Sign up to set email alerts
|

Application of magnifying narrow-band imaging endoscopy for diagnosis of early gastric cancer and precancerous lesion

Abstract: BackgroundGastric carcinoma is the second commonest cause of cancer deaths worldwide. Early detection and diagnosis of gastric cancer in the stomach is important for improving the prognosis of gastric cancer. This retrospective study was designed to investigate the value of magnifying narrow-band imaging (NBI) in the diagnosis of precancerous lesions and early gastric cancer.MethodsThis study included 122 patients who were diagnosed with early gastric cancer or precancerous gastric lesions by endoscopy. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 28 publications
(31 reference statements)
1
24
0
1
Order By: Relevance
“…Additionally, Correa's model of human gastric carcinogenesis has been accepted, which represents apparent sequential steps as follows: chronic superficial gastritis, chronic atrophic gastritis, intestinal metaplasia, dysplasia, and gastric cancer. It is known to all that if gastric cancer can be detected in early stage, the prognosis for it is excellent, the survival rate is greater than 90% in 5 years, and curative endoscopic resection may be possible in some cases of EGC and precancerous gastric lesions . Thus, in this study, PGLs include chronic atrophic gastritis, intestinal metaplasia, neoplasia, and hyperplasia.…”
Section: Methodsmentioning
confidence: 89%
“…Additionally, Correa's model of human gastric carcinogenesis has been accepted, which represents apparent sequential steps as follows: chronic superficial gastritis, chronic atrophic gastritis, intestinal metaplasia, dysplasia, and gastric cancer. It is known to all that if gastric cancer can be detected in early stage, the prognosis for it is excellent, the survival rate is greater than 90% in 5 years, and curative endoscopic resection may be possible in some cases of EGC and precancerous gastric lesions . Thus, in this study, PGLs include chronic atrophic gastritis, intestinal metaplasia, neoplasia, and hyperplasia.…”
Section: Methodsmentioning
confidence: 89%
“…Durante el procedimiento se puede utilizar NAC o ácido acético a 1,5% adicional, pero esto no reemplaza su uso previo 79 Es importante una distensión gástrica completa, para explorar toda la superficie gástrica. La utilización de índigo carmín o azul de metileno, la magnificación óptica y el uso de narrow band imaging (NBI) y probablemente otros sistemas de cromoscopia electrónica (FICE o I-Scan) permiten caracterizar mejor las lesiones 80,81 . En Japón, el registro sistemático de imágenes es parte integral de toda EDA.…”
Section: Recomendacionesunclassified
“…It is not certain whether the use of NBI-only in observing the mucosal lesion has more advantage than the use of chromoscopy, but a combined use of NBI with magnifying endoscopy has a definite advantage in observing the microstructure and the microvasculature of the mucosal surface. Practically most studies that reported favorable results in the diagnoses of lesions used both NBI and magnifying endoscopy rather than white light endoscopy or chromoscopy 1-4…”
Section: Nbi With or Without Magnificationmentioning
confidence: 99%